Surgical Outcome of Colon Interposition in Esophageal Cancer Surgery: Analysis of Risk Factors for Conduit-Related Morbidity - Lee, Kanghoon; Kim, Hyeong Ryul; Park, Seung-Il; Kim, Dong Kwan; Kim, Yong-Hee; Choi, Se Hoon (The Thoracic and Cardiovascular Surgeon, 2018)
Background We aimed to assess the feasibility, surgical outcomes, and conduit-related complications of colon interposition in patients with esophageal cancer.Methods Patients with esophageal cancer who underwent colon interposition for esophageal reconstruction between June 2000 and June 2013 were retrospectively reviewed.Results A total of 67 consecutive patients (mean age, 62.2 ± 7.9 years) were enrolled. During this time period, 944 patients underwent esophageal reconstruction using gastric conduit. Twelve patients (17.9%) also received neoadjuvant chemoradiotherapy (nCRT). The median follow-up duration was 44 months (range, 1–168 months); median survival duration was 63 months (range, 1–168 months); and 3- and 5-year overall survival rates were 61.6 and 49.4%, respectively. A total of 43 patients (64.2%) experienced at least 1 postoperative morbidity. According to the Clavien–Dindo grading system, 36 patients (54%) experienced postoperative morbidity of higher than Grade III. Pulmonary complications were most commonly observed complications among the patients (18 patients, 26.9%). Anastomosis site leakage developed in 11 patients (16.4%), and 3 of these patients (6.0%) eventually experienced graft failure. On multivariate analysis, nCRT was determined as a significant risk factor for conduit-related complications (leakage, graft failure, fistula, and stricture).Conclusion Colon interposition is associated with relatively high complication rates, whereas nCRT is associated with conduit morbidity.
Keywords: esophageal cancer; colon interposition; neoadjuvant chemoradiotherapy; morbidity